การเปลี่ยนแปลงโครงสร้างจุลภาคและสมบัติทางกลของเงินสเตอร์ลิง เกรด 935 ด้วยการเติม 0.3% Sn และ 0.3% Al Microstructural changes and mechanical properties of sterling silver grade 935 with 0.3% Sn and 0.3% Al additions - นิสารัตนพร เอกสิทธิ์; ไชยฤกษ์ นวรัตน์; สกุลตันเจริญชัย สิริวรรณ; ไชยเรืองศรี ธรณินทร์ (Science Essence Journal, 2016)
บทคัดย่อ ในงานวิจัยนี้ได้ศึกษาความสัมพันธ์ของธาตุผสมทองแดง ดีบุก และอะลูมิเนียมที่มีต่อโครงสร้างจุลภาค สมบัติความต้านทานการหมองและสมบัติทางกลของโลหะเงินสเตอร์ลิงเกรด 935 สำหรับผลิตเป็นสปริงเครื่องประดับที่ผลิตขึ้นด้วยวิธีการหล่ออินดักชันและเติมธาตุอะลูมิเนียมและดีบุกในปริมาณ 0.3% โดยน้ำหนัก ผลการวิจัยชี้ชัดว่าอะลูมิเนียมช่วยยับยั้งการเกิดทองแดงออกไซด์ที่ผิวของชิ้นงานสภาพหลังหล่อและนำไปสู่สีผิวที่หมองคล้ำน้อยกว่าผิวของโลหะผสมกลุ่มอื่น การเติมดีบุกทำให้โครงสร้างยูเทคติกมีปริมาณลดลงอย่างเห็นได้ชัดและขนาดเฟสเบตาใหญ่ขึ้น ในการทดสอบการหมองอะลูมิเนียมส่งผลให้ความต้านทานการหมองของโลหะผสมสูงขึ้น สมบัติทางกลทั้งความเป็นสปริงและความต้านทานการดึงสามารถเพิ่มขึ้นอย่างมากด้วยกระบวนการอบด้วยความร้อนปราศจากการอบเป็นเนื้อเดียว การบ่มที่อุณหภูมิ 350oC ส่งผลให้สมบัติทางกลดีกว่าที่อุณหภูมิ 400oC ค่าความเป็นสปริงในโลหะผสมทองแดง อะลูมิเนียมและดีบุก ที่อุณหภูมิ 350oC มีค่า 4.2-4.6, 2.5-3.0 และ1.0-2.0 MPa ตามลำดับ สิ่งนี้เป็นผลมาจากการแตกต่างของโครงสร้างจุลภาค ปริมาณทองแดงในเนื้อพื้น ปริมาณธาตุผสมในเฟสเบตา อุณหภูมิการบ่ม ฯลฯ โลหะเงินผสมทองแดงที่เติมอะลูมิเนียม 0.3% โดยน้ำหนักในงานวิจัยนี้เหมาะสมอย่างมากสำหรับสปริงเงิน คำสำคัญ: โลหะเงินผสม โลหะเงินสเตอร์ลิง กรรมวิธีการอบด้วยความร้อน การอบโดยปราศจากการอบเนื้อเดียว การบ่ม ความเป็นสปริง โครงสร้างจุลภาค — ABSTRACT In this research the relationships of copper tin and aluminium alloy elements on microstructure anti-tarnish property and mechanical properties of sterling silver grade 935 have been studied for manufacturing the jewelry spring which produced with induction casting process and 0.3%wt aluminium and tin additions. The results indicated that aluminium assisted to inhibit the occurrence of copper oxides on the surface of as cast specimens and led to less surface’s tarnish than that of other specimens. An addition of tin gave clearly the less amount of eutectic structure than the other elements’ additions and the size of beta grain increase. In tarnish testing aluminium provided an increase in anti-tarnish property. Mechanical properties including spring and tensile properties greatly improved with the heat treatment in which the solution treatment was ignored. Aging treatment at the temperature of 350oC improved the mechanical properties more than that of 400oC. Spring values of those alloys at the aged condition of 350oC were 4.2-4.6, 2.5-3.0 and 1.0-2.0 MPa respectively. This was attributed to the difference of microstructure, the amount of copper in matrix, the amount of alloying elements in beta phase, aging temperature etc. The silver-copper-aluminium (0.3%wt) silver alloy in this research is very suitable for silver spring application. Keywords: Silver alloys, Sterling silver, Heat treatment, Non-solutionization aging treatment, Aging, Spring property, Microstructure